Analisis Yuridis Pelaksanaan Penghapusan Hak Tanggungan dan Akta Konsen Roya - Mandiri, Dita Ayu; Mediawati, Noor Fatimah (Indonesian Journal Publisher, 2024)
In today's society, mortgage rights are said to be rights to grant land rights with collateral for loans made to banks. Mortgage rights as an agreement on the main collateral, namely the agreement on accounts payable. In order to get a certificate of legal certainty, the mortgage must be converted into a deed of granting the mortgage and registered at the land agency office and also paid off after the debt ends. Roya which is the removal of collateral for mortgage rights which are used as the principal mortgage rights, which have expired or been canceled due to the expiration of the loan by land registration at the request of the party concerned. The purpose of this study is to find out the Juridical Analysis of the Implementation of the Abolition of Mortgage Rights and the Roya Consent Deed using normative juridical research methods. The results and discussion obtained are to remove/delete the mortgage right, the land office signs the roya consent deed and the introductory document. The Roya consent deed must contain an encumbrance right in order to cross out the mortgage right for a requirement or document has been lost.